Sources of conflict and conflict management styles in temporary work environment: A case of plant turnaround maintenance workers - Musah, A.A. (Inderscience Enterprises Ltd., 2017)
This study explored common sources of conflict during plant turnaround maintenance (TAM) project and the intensity of these conflicts. Also examined are the conflict management styles used by TAM workers and how these choices are influenced by individual and organisational factors. Data was gathered from 21 petrochemical companies in East and West Malaysia. Results revealed the commonest sources of conflict are conflict over schedule and sequencing of work, communication breakdown and personality issues. Integrating was the most utilised conflict management style and the least used was compromising. The results also highlighted a predictive relationship between organisational and individual factors and conflict management style, reiterating the fact that organisational and individual characteristics contributes to the management of conflict. The findings were discussed in relation to conflict management in stable organisation. The novelty of this study lies in finding the major sources of conflict and conflict management styles in TAM in Malaysia. Copyright © 2017 Inderscience Enterprises Ltd.